Osteoarthritis and ageing - Valdes, Ana M.; Stocks, Joanne (European Medical Group, 2018)
Ageing is a complex process of accumulation of molecular, cellular, and organ damage, leading to loss of function and increased vulnerability to disease and death, the rate and extent of which varies among individuals. Osteoarthritis (OA) is not only the most common joint disease, but is also one of the major causes of disability in people aged >65 years and is accompanied by comorbid conditions, increased mortality, and decreased quality of life. One of the major risk factors for OA is ageing. However, OA itself may be involved in the biological ageing process. This is likely to be in part a direct involvement, by contributing levels of systemic inflammation and sharing molecular pathways with biological ageing, such as mitochondrial damage leading to cell senescence. Although OA is not considered an inflammatory form of arthritis, there is evidence of subclinical low-grade inflammation in the whole joint and inflammatory processes play a key role in the disease pathogenesis. For instance, there is synovial inflammation (e.g., following injury), mechanically derived inflammation present due to biomechanical overloading of a joint, and systemic inflammation resulting from obesity. Systemic inflammation is often associated with frailty, and having a high concentration of inflammatory markers is predictive of incident frailty, some of which are known to increase with age and correlate with pain. In addition, OA may also contribute indirectly to biological ageing via the disability and pain resulting from it. Further research into the exact process linking OA and biological ageing, including frailty, is needed.